Acupuncture for postherpetic neuralgia: a systematic review protocol - Li, Wang (BMJ Open, 2014)
INTRODUCTION: Postherpetic neuralgia (PHN) is one of the most common complications following herpes zoster. Clinical trials indicate that acupuncture could reduce pain and discomfort among patients with PHN. This protocol aims to describe how to accumulate the current evidence on the efficacy and safety of acupuncture for treating PHN. METHODS AND ANALYSIS: This systematic review will electronically search multiple databases including the Cochrane Skin Group Trials Register, MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL), the Chinese Biomedical Literature Database (CBM), the Chinese Medical Current Content (CMCC) and the China National Knowledge Infrastructure (CNKI), and will hand search a list of medical journals as a supplement. Any clinical randomised controlled trials related to acupuncture for treating PHN will be included. Outcomes will include pain intensity, global impression, quality of life, safety and costs. By screening the titles, abstracts and full texts, two reviewers will independently select studies, extract data, and assess study quality. Meta-analysis of randomised controlled trials will be conducted using Revman 5.1 software. The results will be presented as risk ratio for dichotomous data, and standardised or weighted mean difference for continuous data. ETHICS AND DISSEMINATION: This systematic review does not need ethical approval because there are no data used in our study that are linked to individual patient data. Also, the findings will be disseminated through a peer-review publication or conference presentation. TRIAL REGISTRATION NUMBER: PROSPERO registration number: CRD42014009555.